REVIEW OF PRODUCTION PLANNING AND SCHEDULING: A CASE OF BOOTS CONTRACT MANUFACTURING (BCM) - KISIRKOI, CALEB LEKISHON (2016)
The focus of this research is production planning and scheduling in manufacturing enterprises, using the case study of Boots Contract Manufacturing (BCM). This study is important so as to relate the theory and practice of production planning and scheduling in manufacturing settings with a view to explore optimisation methods. BCM management officially called for the study to be carried out so as to review their overall process of production planning and scheduling and provide some insights into possible areas for improvement. The research approach adopted in this dissertation includes the use of a case study (BCM). Primary and secondary data were collected and used. A numerical example of a scheduling problem was modelled and implemented using LEKIN scheduling system by applying selected dispatching rules and heuristics. Schedules were developed and compared with respect to performance objectives. The findings from this research show that some dispatching rules are effective in optimising certain performance objectives such as makespan, total flowtime and tardiness although none was found to be the best in every measure, requiring trade-offs such as between efficiency and compliance with due dates. The conclusions drawn include that in general dispatching rules are better in developing schedules as opposed to manual scheduling and some dispatching rules perform better in parallel machine environment than in single machine environment. This study recommends that BCM might explore integrating dispatching rules and heuristic methods in their scheduling process, as well as the use of newer information systems with better optimisation capabilities would possibly improve the production planning and scheduling process in BCM.